Cotton Fiber Moisture Measurements: A Comparative Evaluation. Issue 5 (September 2014) - Rodgers, James; Fortier, Chanel; Kang, Sho Yeung; Montalvo, Joseph; Von Hoven, Terri
A commonly-used standard method for measuring cotton fiber moisture is the oven-drying method (moisture content equal weight loss). However, several commercial instruments are available for measuring fiber moisture content. A comparative evaluation program was implemented to determine the capabilities of laboratory moisture instrumentation/methods and to develop a standard format to quickly compare different units (logistical and technical attributes). Fifteen instruments were evaluated and compared to an oven-drying (reference) method. The best measurement agreements to the reference method were obtained for most small oven analyzers and near-infrared (NIR) analyzers, with few outliers and low residuals. A comprehensive comparative matrix was developed to assist the user decision-making process for selecting the best overall instrument to meet their fiber moisture measurement needs.